2014
DOI: 10.1007/s40265-013-0173-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Treatment of Psoriasis Reduce the Risk of Cardiovascular Disease?

Abstract: Psoriasis is an inflammatory disease associated with multiple comorbidities and cardiovascular risk factors. Patients with psoriasis have an increased risk of cardiovascular disease (CVD) and cardiovascular death. It has been proposed that overlapping mechanisms of systemic inflammation contribute to the link between psoriasis and cardiovascular disease. Some psoriasis treatments decrease systemic inflammation, but the effect of psoriasis treatments on heart disease is unknown. In this review of 23 original re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
0
13
0
2
Order By: Relevance
“…Churton et al (5) reviewed twenty-three original research publications, and presented preliminary evidence that some psoriasis therapies improve cardiovascular biomarkers and the incidence of cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Churton et al (5) reviewed twenty-three original research publications, and presented preliminary evidence that some psoriasis therapies improve cardiovascular biomarkers and the incidence of cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of the TNF-a inhibitors therapy with infliximab, etanercept and adalimumab has intensely enhanced the outcome of severe psoriasis further than that achieved with traditional systemic drugs. Both MTX and TNF-a inhibitors improve cardiovascular inflammatory biomarkers and CVD outcomes (5). A cardioprotective effect has been suggested with systemic agents such as MTX and TNF-a inhibitor agents in rheumatoid arthritis and psoriasis populations (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent data from more than 8845 patients enrolled the Kaiser Permanente Southern California health plan suggested that treatment of psoriasis with tumor necrosis factor (TNF) inhibitors was associated with a significant reduction in myocardial infarction risk and incidence rate compared with the treatment with topical agents . Moreover, systemic treatment with methotrexate or photo(chemo)therapy, including broadband UV‐B, narrowband UV‐B or PUVA , was also associated with a significant reduction in cardiovascular risk. Interestingly, a small study demonstrated recently that treatment of psoriasis utilizing anti‐TNF therapy led to improvement in carotid intimal‐medial thickness, an established surrogate marker of cardiovascular disease .…”
Section: Effective Antipsoriatic Therapy Improves Hdl Composition Andmentioning
confidence: 99%
“…Usually, the subjects were defined as having moderate to severe psoriasis if they had a history of systemic treatments. However, some psoriasis therapies may increase incidence of cardiovascular diseases while others may decrease it 1 2 . These heterogenous effects of individual drugs on cardiovascular disease may limit current practice of determining the severity according to past treatment history, in the aspect of evaluating the current cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%